Investigation of the incidence of immunisation stress-related response following COVID-19 vaccination in healthcare workers. Issue 6 (June 2022) - Takano, Tomonori; Hirose, Masanori; Yamasaki, Yukitaka; Hara, Masatoshi; Okada, Tomoyuki; Kunishima, Hiroyuki
Abstract: Introduction: Safe vaccination worldwide is critical to end the coronavirus disease 2019 (COVID-19) pandemic. We aimed to evaluate adverse reactions to vaccination using a web-based questionnaire and examine the risk factors for the occurrence of immunisation stress-related response (ISRR). Methods: We conducted a questionnaire survey using Google Form® among the employees of St. Marianna University Hospital who had received the COVID-19 vaccine between April 2021 and May 2021, 1 week after the first and second vaccinations. We developed and used a questionnaire to identify individuals with ISRR according to the World Health Organization diagnostic criteria. A generalised linear mixed model was constructed with ISRR onset as the dependent variable, subjects as the random factor, and each parameter as a fixed factor. A multivariate model was constructed using the forced imputation method with factors that were significant in the univariate analysis. Results: We enrolled 2, 073 and 1, 856 respondents in the first and second questionnaire surveys, respectively. Fifty-five and 33 ISRR cases were identified in the first and second vaccinations, respectively. In the univariate analysis, strong pre-vaccination anxiety (odds ratio [OR], 2.3; 95% confidence interval [CI], 1.30–4.12, p = 0·004) and history of allergy (OR, 1.6; 95% CI, 1.14–2.24, p = 0·007) were significant risk factors. Multivariate analysis also showed that strong pre-vaccination anxiety (OR, 2.1; 95% CI, 1.15–3.80, p = 0.016) and history of allergy (OR, 1.5; 95% CI, 1.09–2.15, p = 0.014) were significant risk factors. Conclusions: Confirmation of allergy prior to vaccination and subsequent action are essential for addressing ISRR.